2016
DOI: 10.1016/j.celrep.2016.03.072
|View full text |Cite|
|
Sign up to set email alerts
|

Polq-Mediated End Joining Is Essential for Surviving DNA Double-Strand Breaks during Early Zebrafish Development

Abstract: Summary Error-prone repair of DNA double-strand breaks (DSBs) has been postulated to occur through classical non-homologous end joining (NHEJ) in systems ranging from nematode somatic tissues to zebrafish embryos. Contrary to this model, we show that zebrafish embryos mutant for DNA polymerase theta (Polq), a critical component of alternative end joining (alt-EJ), cannot repair DSBs induced by CRISPR/Cas9 or ionizing radiation. In the absence of DSBs, polq mutants are phenotypically normal, but they do not sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 49 publications
2
49
0
Order By: Relevance
“…The clear contribution of TMEJ in genetically non-compromised embryonic stem cells agrees well with the observation that DSB-induced translocation formation in mouse embryonic cells and in mice models is mostly cNHEJ independent (Weinstock et al, 2007;Simsek & Jasin, 2010;Mateos-Gomez et al, 2015). Intriguingly, the apparent shift in end-joining pathway usage towards TMEJ in cells that have a more stem-cell like character is also found in other species: in the model systems C. elegans and zebrafish TMEJ is the dominant mode of (error-prone) DSB repair in germ and embryonic cells; somatic cells, however, employ mostly cNHEJ Thyme & Schier, 2016). In agreement, Wyatt and colleagues recently showed that mouse embryonic fibroblasts (MEFs) preferentially use cNHEJ to repair Cas9-induced blunt DSBs leading them to conclude that TMEJ functions merely as a back-up mechanism.…”
Section: Tmej Acts Parallel To Cnhej In Embryonic Cellsmentioning
confidence: 93%
“…The clear contribution of TMEJ in genetically non-compromised embryonic stem cells agrees well with the observation that DSB-induced translocation formation in mouse embryonic cells and in mice models is mostly cNHEJ independent (Weinstock et al, 2007;Simsek & Jasin, 2010;Mateos-Gomez et al, 2015). Intriguingly, the apparent shift in end-joining pathway usage towards TMEJ in cells that have a more stem-cell like character is also found in other species: in the model systems C. elegans and zebrafish TMEJ is the dominant mode of (error-prone) DSB repair in germ and embryonic cells; somatic cells, however, employ mostly cNHEJ Thyme & Schier, 2016). In agreement, Wyatt and colleagues recently showed that mouse embryonic fibroblasts (MEFs) preferentially use cNHEJ to repair Cas9-induced blunt DSBs leading them to conclude that TMEJ functions merely as a back-up mechanism.…”
Section: Tmej Acts Parallel To Cnhej In Embryonic Cellsmentioning
confidence: 93%
“…POLQ's critical role in Alt-EJ-mediated DSB repair has been demonstrated in various animal organisms, such as Caenorhabditis elegans, flies, zebrafish, mice and human (Chan et al, 2010;Roerink et al, 2014;Kent et al, 2015;Mateos-Gomez et al, 2015;Thyme & Schier, 2016). POLQ was shown to be a key driver of CRISPR-Cas9 DSB repair leading to mutagenesis in C. elegans (van Schendel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Alt-NHEJ was initially thought to act as a back-up mechanism 2 , however, recent studies revealed that it operates even when HR and C-NHEJ are intact 3 . Alt-NHEJ is a major repair pathway during early vertebrate development 4 . Moreover, when HR and C-NHEJ are impaired, mammalian cells become highly dependent on alt-NHEJ for survival 57 .…”
Section: Introductionmentioning
confidence: 99%
“…Its activity was first linked to alt-NHEJ during P-element transposition in flies 10 , and later found to promote end-joining in plants 11 , worms 12 , fish 4 , and mammals 5,6,1315 . Mammalian Polθ stimulates alt-NHEJ in response to endonuclease-mediated cleavage of reporter constructs 5,6,13,14 , drives the fusion of dysfunctional telomeres 5 , and promotes chromosomal translocations in mouse embryonic stem (mES) cells 5 .…”
Section: Introductionmentioning
confidence: 99%